Karakteristik Serat Tandan Kosong Kelapa Sawit Sebagai Komposit Resin Polyester Untuk Mengetahui Nilai Absorpsi Suara - Mar'i Akbar, Firzan; Napitupulu, Robert; Yudo, Eko (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
The development of composite materials currently not only with synthetic reinforcing materials but also with natural fiber reinforcing materials, because natural fibers have diverse characteristics. In this research, looking at the characteristics of Oil Palm Empety Fruit Bunch (OPEFB) fiber which has a high cellulose and hemicellulose content, which is generally used for soundproofing materials. So a composite research will be made from the main material of OPEFB fiber with polyester resin as the matrix. The purpose of this research is to determine the sound absorption value of the composition of the mixture of OPEFB fiber and resin. The method used is the hand lay-up method combined with the Taguchi Method on the L4(23) orthogonal matrix design used as a reference for the sound absorbing composite manufacturing process. The L4(23) orthogonal matrix design is used because there are three process parameters that have two levels. Repetition is repeated three times. The process parameters are the volume fraction of OPEFB fiber and resin, the length of fiber soaking with NaOH, and the thickness of the composite. The research results from three repetitions obtained the highest value in sample I with a mean value = 77.93 dB at a frequency of 2000 Hz, and the lowest value in sample III with a mean value = 32.97 dB at a frequency of 125 Hz.